Natural groups and economic characteristics as driving forces of wage discrimination - Chmura, Thorsten; Goerg, Sebastian J.; Weiss, Pia (Elsevier, 2016)
We investigate whether the origin of an employee provides different motives for wage discrimination in gift-exchange experiments with students and migrant workers in China. In a lab and an internet experiment, subjects in the role of employers can condition their wages on the employees׳ home provinces. The resulting systematic differences in wages can be linked to natural groups and economic characteristics of the provinces. In-group favoritism increases wages for employees who share the same origin as the employer, while an increased probability of being matched with an employee with a different ethnicity reduces wages. Furthermore, wages in the laboratory increase with the actual wage level in the employees׳ home province. Nevertheless, employees׳ effort is not influenced by these variables; only the wage paid in the experiment influences effort.